2021
DOI: 10.1136/bmjopen-2020-045592
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic, geographic and health system factors associated with rising C-section rate in Indonesia: a cross-sectional study using the Indonesian demographic and health surveys from 1998 to 2017

Abstract: IntroductionCaesarean section (C-section) has been a public health concern globally. This study investigated the change in C-section rate in 1998–2017 in Indonesia and explored the socioeconomic, geographic and health system factors associated with the use of C-section.MethodsWe analysed data from demographic health surveys in 2002–2003, 2007, 2012 and 2017 in Indonesia. We included women who reported giving birth within 5 years of each round of the survey (n=56 462) into the analysis. Cross-tabulation was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
(19 reference statements)
1
14
0
Order By: Relevance
“…(19) Women's socioeconomic status and health system factors were associated with the increased use of CS. (20) In contrast, a Bangladesh study found that the logistic regression analysis has traced no significant variation in CS rate among mothers of varying educational levels as compared to the reference group (mothers with no education) (p>0.05). Similarly, mothers' religious status, age at first childbirth, age at first marriage, working status, exposure to media, including wanted indexed child and husband's educational level, resulted in no significant difference in CS rate among various groups as compared to their corresponding reference groups.…”
Section: Introductionmentioning
confidence: 90%
“…(19) Women's socioeconomic status and health system factors were associated with the increased use of CS. (20) In contrast, a Bangladesh study found that the logistic regression analysis has traced no significant variation in CS rate among mothers of varying educational levels as compared to the reference group (mothers with no education) (p>0.05). Similarly, mothers' religious status, age at first childbirth, age at first marriage, working status, exposure to media, including wanted indexed child and husband's educational level, resulted in no significant difference in CS rate among various groups as compared to their corresponding reference groups.…”
Section: Introductionmentioning
confidence: 90%
“…This indicates that there has been a decrease in normal vaginal delivery in recent years (Bhandary, 2017;Borem et al, 2020). The increase in the average trend of cesarean sections also occurred in Indonesia, from 2% in 1991 to 16% in 2012 (Wyatt et al, 2021). Even though most of the causes of cesarean sections were due to obstetric complications, the concern about excessive pain during delivery and inability to wait for normal delivery, which usually takes quite a long time, also caused an increase in cesarean sections in those times (Sungkar & Basrowi, 2020;Sungkar et al, 2019).…”
Section: Introductionmentioning
confidence: 97%
“…However, the increasing trend in a cesarean section has continued in the last few decades, from 6.7% in 1990 to 19.1% in 2014 (Wyatt et al, 2021). This indicates that there has been a decrease in normal vaginal delivery in recent years (Bhandary, 2017;Borem et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Cesarean section (C-section) is becoming more popular as a delivery method. C-section rates have risen worldwide from 4% in 1998 [1] to 21.1% in 2018 [2], while, in Indonesia, they have risen from 9.8% in 2013-18.5% in 2017 [3], [4]. With the increasing numbers of C-sections performed each year, proper anesthetic and post-operative pain management are critical for better results [2].…”
Section: Introductionmentioning
confidence: 99%